2000
DOI: 10.1029/2000jd900438
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year east Asian summer monsoon simulation using a regional climate model (RegCM2)

Abstract: Abstract. This paper presents a 10-year (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 26 publications
3
88
0
4
Order By: Relevance
“…This tendency did not occur only in the PRM. Previous studies using different regional models also found a similar bias (e.g., Lee and Suh 2000;Wang et al 2003;Y.-H. Ding, personal communication). Similar bias occurred in models with very different designs, indicating the possible existence of an unsolved fundamental problem.…”
Section: Conclusion and Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…This tendency did not occur only in the PRM. Previous studies using different regional models also found a similar bias (e.g., Lee and Suh 2000;Wang et al 2003;Y.-H. Ding, personal communication). Similar bias occurred in models with very different designs, indicating the possible existence of an unsolved fundamental problem.…”
Section: Conclusion and Discussionmentioning
confidence: 63%
“…The simulated southwesterly was much too strong in southern China in July, corresponding to the excessive precipitation in the area. In August, the synoptic-scale anticyclone south of Japan and the corresponding strong southwesterly in the northern part of this domain were the major circulation features associated with the anomalous precipitation in Korea (out of the range of the plot; Lee et al 2002). The PRM did not capture the synoptic-scale anticyclone, and therefore underestimated the strength of the southwesterly and the precipitation.…”
Section: Seasonal and Monthly Meansmentioning
confidence: 99%
See 3 more Smart Citations